IMPROVING STUDENTS’ WRITING ABILITY IN DESCRIPTIVE TEXT THROUGH CLUSTERING TECHNIQUE AT TENTH GRADE of MA MA’ARIF ROUDHOTUT THOLIBIN METRO - Desi Dwi Suryani; Anindya Muhti Apriliani (Journal of English Development, 2021)
The objective of this research was to improve the students’ writing ability in descriptive text through clustering technique at the tenth grade of MA Ma’arif Roudhotut Tholibin Metro in academic year 2018/2019. This research was conducted at tenth grade in second semester at MA Ma’arif Roudhotut Tholibin Metro in academic year 2017/2018. The design of this research was classroom action research (CAR). This research was applied collaborative action research, this research was done in two cycle. It is done with; planning, acting, observation and reflecting. In collecting data, the writer uses; test,observation and questionnaire. the application of the clustering technique could improve the students’ writing ability in descriptive text. Based on the results of the observation obtained the students more understanding to make descriptive sentences, and make the descriptive sentences into a descriptive text. The activity make the student become interested to describe the pictures or object, students more active and more anthusiasm in the writing learning process. Then, in Cycle 1 students passed is 15 (60%). In cycle 2 students passes the KKM (80%). Was improved 20% in cycle 2. By this number, the researcher concludes that the minimum target of success, that is 70% of the students in a class, has been achieved in cycle 2, and from the third data we can conclude it was prove that clustering technique can positively improve the students’ writing ability in descriptive text at tenth grade of MA Ma’arif Roudhotut Tholibin Metro in academic year of 2018/2019 Keyword : Improve Student’s Writing, Descriptive Text, Clustering technique.